Integrating an MPSoC to a Robotics Environment - Domingues, Anderson; Jurak, Darlan; Filho, Sergio; Amory, Alexandre (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Multiprocessor system-on-chip (MPSoC) have been successfully used to speed up the processing of parallel, computing-intensive applications. Many domains could benefit from such processing power, including the one of robotics, in which several tasks, from image processing to odometry, may compete for resources at the same time as they cooperate to achieve system's goals. This paper presents the preliminary results on the integration of an MPSoC to a robotics environment through co-simulation. We developed wrappers to permit two simulators to communicate via UDP networks; While one simulator carries out environmental physics, the other one simulates the underlying MPSoC platform. We provide a proof-of-concept based on a synthetic random-walk application along with a performance analysis of the environment. With this environment, we move towards the evaluation of non-functional requirements of robotics applications, such as energy consumption.